PPARG/SPP1/CD44 signaling pathway in alveolar macrophages: Mechanisms of lipid dysregulation and therapeutic targets in idiopathic pulmonary fibrosis - Ganggang Li; Yuwei Zhang; Huanyu Jiang; Xuanyu Wu; Yanwei Hao; Yuchen Su; Yutong Zou; Wenjia Xian; Fei Wang; Quanyu Du (Heliyon)
Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive interstitial lung disease. It is characterized by inflammation and fibrosis in the lung parenchyma and interstitium. Given its poor prognosis and limited treatment options, understanding the underlying molecular mechanisms is crucial. Recent evidence suggests that lipid metabolism plays a pivotal role in IPF pathogenesis, however, the precise mechanisms remain poorly understood. To address this, we analyzed 12 bulk RNA-seq and 2 single-cell RNA-seq datasets from the GEO database using machine learning approaches. As a result, we identified four key lipid-related genes—PPARG, SPP1, CASP3, and PECAM1—that are expressed across various cell types. Specifically, in alveolar macrophages (AMs), we observed that PPARG was significantly downregulated, while SPP1 was highly expressed. Importantly, PPARG serves as a transcriptional regulator of SPP1, which in turn mediates intercellular signaling via CD44. Based on these findings, we propose a novel PPARG/SPP1/CD44 signaling pathway in AMs, which modulates lipid metabolism and likely contributes to the progression of fibrosis in IPF. Moreover, network pharmacology analysis identified several herbal compounds that target PPARG, offering potential therapeutic opportunities. In conclusion, these findings highlight the critical role of lipid metabolism in IPF and present novel molecular targets for the development of future therapeutic strategies.